Evaluating multiannual sedimentary nutrient retention in agricultural two-stage channels - Kaisa Västilä; Tom Jilbert (Scientific Reports)
Abstract The two-stage channel (TSC) design with a vegetated man-made floodplain has been recommended as an alternative to conventional re-dredging for managing suspended sediment (SS) and nutrient loads in agricultural streams. However, there are currently uncertainties surrounding the efficiency of TSCs, since mass balances covering the whole annual hydrograph and including different periods of the channel life cycle are lacking. This paper aims to improve understanding of the medium-term morphological development and sedimentary nutrient retention when a dredged, trapezoidal-shaped channel is converted into a TSC, using a mass balance estimate of nutrient and carbon retention from immediately after excavation until the establishment of approximate biogeochemical equilibrium retention. We developed a framework allowing estimation of the sedimentary net retention of phosphorus (P), nitrogen (N) and carbon (C) considering the differences in the initial and mature biogeochemical conditions in topsoil between different channel parts. Further, we conducted repeated elevation surveys and analyses of vertical sedimentary elemental chemistry over a 9-year period to apply the framework at a pilot site in Southern Finland. The pilot TSC floodplain significantly retained SS and nutrients while the low-flow channel did not suffer from siltation, supporting the hypothesized enhanced self-cleansing capacity of TSCs compared to trapezoidal cross-sections. Because of the flushing of the earlier bed deposits, there was net release of SS, P, and N over the first 9 years in the entire TSC system. Depending on the element and channel part considered, physical deposition constituted 13‒79% of the net retention on the newly exposed, excavated surfaces, while the remainder could be attributed to biogeochemical retention, enriching the topsoil in nutrients and carbon. The developed framework is highly suitable to assess the medium-term sedimentary nutrient retention in TSC systems. As a novelty, the framework improves the reliability of the retention efficiency evaluation compared to the typically used snapshot water quality sampling and allows prioritizing the required sediment coring at further TSC sites. The results allow heterogeneities in the process rates to be quantified and potential inefficiencies in nutrient retention due to channel design and morphology to be identified.